Sassy. The birthday storm - Draper, Sharon M. (Sharon Mills) (New York : Scholastic, 2009)
While in Florida to celebrate her Grammy's birthday, nine-and-a-half-year-old Sassy worries that an approaching hurricane will ruin not only the party, but a nest of sea turtle eggs, as well. Includes facts about hurricanes and sea turtles.
Accelerated Reader AR
Keywords: Hurricanes -- Juvenile fiction; Birthdays -- Juvenile fiction; Grandparents -- Juvenile fiction; Families -- Florida -- Juvenile fiction; Sea turtles -- Juvenile fiction; African Americans -- Juvenile fiction; Florida -- Juvenile fiction